2001
DOI: 10.1119/1.1308266
|View full text |Cite
|
Sign up to set email alerts
|

Waves in locally periodic media

Abstract: We briefly discuss the possibility to describe with a formalism, analogous to the Bragg law and the transfer matrix method used for photonic crystals, the behaviour of the kinetic energy of an object travelling through a one-dimensional (1D) modulation of the gravitational interaction, i.e. a 1D gravitational crystal. We speculate that certain ranges of the kinetic energy of an object with mass m and speed v cannot travel through the crystal, giving rise to a gravitational gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
192
1
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(205 citation statements)
references
References 59 publications
3
192
1
6
Order By: Relevance
“…Consider the case that v 0 (x) = 0 and the perturbation involves an array of Dirac delta-functions [13][14][15][16]:…”
Section: Array Of Complex Delta-function Potentialsmentioning
confidence: 99%
“…Consider the case that v 0 (x) = 0 and the perturbation involves an array of Dirac delta-functions [13][14][15][16]:…”
Section: Array Of Complex Delta-function Potentialsmentioning
confidence: 99%
“…[2][3][4][5] In this way, the transfer matrix formalism provides a simple mathematical tool allowing for a unified treatment of such diverse problems as electron or phonon dynamics in both periodic and aperiodic lattices, [6][7][8][9][10][11][12][13][14][15][16] optical properties of dielectric multilayers, [17][18][19][20][21] the propagation of acoustic waves in semiconductor heterostructures and metallic superlattices, [22][23][24] localization of elastic waves in heterogeneous media, 25 or charge transport through DNA chains. [26][27][28][29][30] A significant number of works have focused on the study of systems based on two simple kinds of transfer matrices, namely, the so-called on-site and transfer models.…”
Section: ͑3͒mentioning
confidence: 99%
“…On the other hand, in a series of works devoted to the study of periodic superlattices it was reported that Chebyshev polynomials play, for finite systems, a similar role to the one played by the Bloch functions in the description of transport properties of infinite periodic systems. [40][41][42] In addition, the ability of these polynomials to properly describe the propagation of both quantum and classical waves in locally periodic media ͑namely, systems having only a relatively small number of repeating elements͒ in a compact way has been recently illustrated, 43 as well as their convenience when describing the presence of extended states in correlated random systems. 44,45 …”
Section: Introductionmentioning
confidence: 99%